Analysis of Stability, Resistance, and Seakeeping Accord to Dimension and Form of Fishing Vessel 10, 20, 30 GT - Rizky Irvana; Arif Fadillah; Shanty Manullang; Fridolini Fridolini (Universitas Lampung, 2019)
Fishing vessels used to catch resources from the sea has to pass some of the regulations from International Maritime Organization for sea-worthiness of the vessel especially about stability, resistance to acquire the highest velocity, and the vessel’s motion. This research discusses the effect of the vessel’s dimension and the hull shape by using the stability standard from IMO.The result shows that the ratio of the B/T which meets the stability criteria is 2.50 with the ratio of KG/H of the vessel is 0.65, with the assumption that the KG and H of the vessel are more than 0.70. Whereas if the resistance ratio B/T is big, the resistance for the vessel will be relatively smaller. In terms of the vessel motion, a vessel with a V-type hull will better than a U-type hull in seakeeping.